Metagenomic next-generation sequencing as a diagnostic tool for toxoplasmic encephalitis - Zhiliang Hu; Xing Weng; Chunhua Xu; Yang Lin; Cong Cheng; Hongxia Wei; Wei Chen (BMC, 2018)
Abstract Background More than 100 different pathogens can cause encephalitis. Testing of all the neurological pathogens by conventional methods can be difficult. Metagenomic next-generation sequencing (NGS) could identify the infectious agents in a target-independent manner. The role of this novel method in clinical diagnostic microbiology still needs to be evaluated. In present study, we used metagenomic NGS to search for an infectious etiology in a human immunodeficiency virus (HIV)-infected patient with lethally diffuse brain lesions. Sequences mapping to Toxoplasma gondii were unexpectedly detected. Case presentation A 31-year-old HIV-infected patient presented to hospital in a critical ill condition with a Glasgow coma scale score of 3. Brain magnetic resonance imaging showed diffuse brain abnormalities with contrast enhancement. Metagenomic NGS was performed on DNA extract from 300 μL patient's cerebrospinal fluid (CSF) with the BGISEQ-50 platform. The sequencing detection identified 65,357 sequence reads uniquely aligned to the Toxoplasma gondii genome. Presence of Toxoplasma gondii genome in CSF was further verified by Toxoplasma gondii-specific polymerase chain reaction and Sanger sequencing. Altogether, those results confirmed the diagnosis of toxoplasmic encephalitis. Conclusions This study suggests that metagenomic NGS may be a useful diagnostic tool for toxoplasmic encephalitis. As metagenomic NGS is able to identify all pathogens in a single run, it may be a promising strategy to explore the clinical causative pathogens in central nervous system infections with atypical features.